Agile Leadership and its Role in Achieving Strategic Leadership Applying to Egypt Air - Abdel-Bary, Ashraf El-Sayed; Yousef, Sharif Mohamed Mohamed (The Arab Journal of Administration, 2025)
In light of the fierce competition from companies operating in the field of aviation to achieve strategic leadership, organizational agility has become a working method and a basic requirement to provide planners with various future methods to move the company from its past and present framework to accurately anticipate the image of the possible or desired future to achieve this future and prepare for it, its requirements and challenges. Agile leadership is considered one of the essential requirements to support the survival, continuity and success of organizations, as it gives the organization a flexible framework that enables it to excel and lead. The problem of the study can be formulated in the question: What is the role of the dimensions of agile leadership in achieving strategic leadership in EgyptAir? The main objective is to study the relationship of the dimensions of agile leadership (humility, calmness, wisdom, patience, objectivity, trust) and the dimensions of strategic leadership (entrepreneurial culture, entrepreneurial thinking, and strategic management of resources). The analytical descriptive approach was followed: where the basic theoretical concepts related to the subject of the study were identified and rooted, using various references, periodicals, and various scientific sources, extracting ideas from them, and referring to previous studies. study variables. The study reached some results, the most important of which are: There is a moral link between agile leadership and consolidating the pioneering culture in EgyptAir. There is a significant correlation between agile leadership and the development of entrepreneurial thinking capabilities in EgyptAir. There is a significant correlation between agile leadership and the efficiency of strategic resource management in EgyptAir. The sample has, in general, positive attitudes towards the behaviors and practices of agile leadership among the company’s leaders. The sample has, in general, positive trends towards the availability of the elements of the dimensions of strategic leadership in EgyptAir. The study recommended some recommendations, the most important of which are: The necessity of supporting agile leadership behaviors and practices, increasing interest and expanding the use of institutional agility tools and mechanisms in all company sectors. The necessity for the leaders of EgyptAir to adopt a future vision with a pioneering direction for the company based on the principles of institutional agility; To enable it to achieve strategic leadership.